Gambaran resiliensi remaja penderita luka bakar di panti asuhan - Pertiwi, Nesya Ayu; Vinaya, Vinaya; Yudha, Yusuf Hadi (Konsorsium Psikologi Ilmiah Nusantara, 2013)
Fire incidents which have caused wounds and burns may negatively affected for psychological aspect of the victims. A part of physical damages they experienced, the accident may cause lost of family members whom they love, that lead them to live orphanage as they do not have family as well as home and have to face tough conditions and pressures in their lives. Patients with burns who are able to develop resilience capabality can adjust them-selves to adapt well, and even managed to become a better individual. The aim of this research is to know the resilience capability and the factors affecting resilience in adolescence with burns that live in orphanage. This research used qualitative approach with interview and observation in one respondent.This research shows description about that resilience capability in teenager that having burns who live in the orphanage and its risk and protective factors.